Multi-Level Quantum Error Correction in Scalable Quantum Computing Architectures - Kuc, Stefan Grzegorz; Barański, Miłosz (Journal of Applied Automation Technologies, 2023)
Without increasing decoding delay, fault-tolerant quantum processing must lessen the effects of physical noise, measurement errors, leakage errors, and correlated disturbances. A multi-level quantum error correcting architecture for scalable quantum processors is examined in this research. Physical-layer syndrome extraction, logical-layer stabilizer decoding, and architecture-level error propagation control are the three types of correction. To balance the dependability of local rectification with global logical consistency, a comparatively compact noise-aware decoding technique has been presented. According to simulation data, the suggested architecture has enhanced robustness to correlated noise by 31.8%, decreased the average decoding delay by 24.3%, and reduced the logical error rate by 37.6% when compared to a single-level surface-code baseline. According to the findings, the hierarchical correction approach offers a suitable trade-off between accuracy and resource usage for real-time decoding. For large-scale quantum computing systems, the paper offers an engineering-focused correction model that simultaneously takes decoder responsiveness, qubit layout, and logical fidelity into account.